Ballroom Biology: Recent Insights into Honey Bee Waggle Dance Communications - Roger Schurch (Frontiers Research Topics, 2016)
The honey bee waggle dance communication is a complex, unique, at times controversial, and ultimately fascinating behavior. In an elaborate figure-of-eight movement, a returning forager conveys the distance and direction from the hive to resources, usually the nectar and pollen that is their food, and it remains one of the most sophisticated, known forms of non-human communication. Not surprisingly, since its discovery more than 60 years ago by Karl von Frisch, the dance has been subject to investigations that span from basic biology through human culture and neurophysiology to landscape ecology. Here we collate recent advances in our understanding of the dance.